Quantifying the impacts of land use/land cover changes on ecosystem service values in the upper Gilgel Abbay watershed, Ethiopia - Wassie Abuhay Aschenefe; Temesgen Gashaw Tarekegn; Betelhem Fetene Admas; Solomon Mulu Tafere (Regional Sustainability)
Human well-being and livelihoods depend on natural ecosystem services (ESs). Following the increment of population, ESs have been deteriorated over time. Ultimately, land use/land cover (LULC) changes have a profound impact on the change of ecosystem. The primary goal of this study is to determine the impacts of LULC changes on ecosystem service values (ESVs) in the upper Gilgel Abbay watershed, Ethiopia. Changes in LULC types were studied using three Landsat images representing 1986, 2003, and 2021. The Landsat images were classified using a supervised image classification technique in Earth Resources Data Analysis System (ERDAS) Imagine 2014. We classified ESs in this study into four categories (including provisioning, regulating, supporting, and cultural services) based on global ES classification scheme. The adjusted ESV coefficient benefit approach was employed to measure the impacts of LULC changes on ESVs. Five LULC types were identified in this study, including cultivated land, forest, shrubland, grassland, and water body. The result revealed that the area of cultivated land accounted for 64.50%, 71.50%, and 61.50% of the total area in 1986, 2003, and 2021, respectively. The percentage of the total area covered by forest was 9.50%, 5.90%, and 14.80% in 1986, 2003, and 2021, respectively. Result revealed that the total ESV decreased from 7.42×107 to 6.44×107 USD between 1986 and 2003. This is due to the expansion of cultivated land at the expense of forest and shrubland. However, the total ESV increased from 6.44×107 to 7.76×107 USD during 2003–2021, because of the increment of forest and shrubland. The expansion of cultivated land and the reductions of forest and shrubland reduced most individual ESs during 1986–2003. Nevertheless, the increase in forest and shrubland at the expense of cultivated land enhanced many ESs during 2003–2021. Therefore, the findings suggest that appropriate land use practices should be scaled-up to sustainably maintain ESs.